Importance of an arginine-glycine-aspartic acid (RGD) motif in the VP7 protein of African horse sickness virus to mediate insect cell binding - Theron, Jacques (University of Pretoria, 2024)
Dissertation (MSc (Microbiology))--University of Pretoria, 2024.